Effectiveness of Group Counseling Cognitive Behavior Therapy Cognitive Restructuring Technique and Assertive Skill Training to Improve Assertive Behavior Students - Hasibuan, Meli Adriani Hotma; Purwanto, Edy; Japar, Muhammad (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to test the effectiveness of cognitive behavioral therapy group counseling using cognitive restructuring techniques and assertive skills training to improve student assertive behavior. The research method used was experimental, design Pretest-Posttest Randomized Comparison Group Design, involving research subjects were 21 students selected by purposive sampling of class X SMK Ibu Kartini Semarang. The results of analysis by using One way ANOVA showed that group counseling using cognitive restructuring techniques and techniques of assertive skills training is effective in improving student assertive behavior (F = 78.141; p < 0.01). The results of this study showed that students who received counseling services group uses a combination of techniques cognitive restructuring techniques assertive skills training is more effective than counseling group that only received one of the counseling service engineering group cognitive restructuring or by using assertive skills training to improve assertive behavior of students.